Pengaruh Kecerdasan Logika Matematika Terhadap Disposisi Matematis Siswa - Anah Maemanah; Widodo Winarso (Department of Mathematics Education, Faculty of Tarbiyah and Teacher Training, UIN Sunan Ampel Surabaya, 2019)
This study aims to determine the influence of logic smart on students' mathematical dispositions. The method is quantitative with ex post facto approach — the population of class XI MIPA MAN 2 Cirebon and three samples taken by random sampling. Data collection uses logic smart tests and questionnaires was then analyzed using a simple regression test. Analysis and interpretation of data show that logic smart of students at coherent level with the average value is 65.93 and 57%, mathematical disposition of students is at a high level with a percentage of the average indicator value is 70%, and there is a significant influence between logic smart with the mathematical disposition of 63.2% and a significance value of 0.00<0.05. So, the teacher should improve the logic of smart students through logical thinking, as well as counting ability accompanied by observations to solve mathematical problems because it has implications for the ability of students' mathematical dispositions.